-76=3x-6x+1

Simple and best practice solution for -76=3x-6x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -76=3x-6x+1 equation:


Simplifying
-76 = 3x + -6x + 1

Reorder the terms:
-76 = 1 + 3x + -6x

Combine like terms: 3x + -6x = -3x
-76 = 1 + -3x

Solving
-76 = 1 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
-76 + 3x = 1 + -3x + 3x

Combine like terms: -3x + 3x = 0
-76 + 3x = 1 + 0
-76 + 3x = 1

Add '76' to each side of the equation.
-76 + 76 + 3x = 1 + 76

Combine like terms: -76 + 76 = 0
0 + 3x = 1 + 76
3x = 1 + 76

Combine like terms: 1 + 76 = 77
3x = 77

Divide each side by '3'.
x = 25.66666667

Simplifying
x = 25.66666667

See similar equations:

| 9(k-1)=36 | | d-16+5d=14 | | y-(-1)=7/8(x-9) | | 3g+5=26 | | 2n+8=6n | | 0=4x^2+5x-2 | | 3x+2(x+6)=37 | | 6=3(3j-4) | | 6r^2-12r-20=-9 | | 12=4(2m+5) | | 4(2x+7)-8=60 | | -6(d+2)=12 | | -3(2+y)=48 | | 17x^2-13x-2=0 | | 7c-5d-6c+4d= | | 81m^2-64m^2/9x-8x | | y=-3x(-2) | | a(12+8)=54 | | (ax-12b)(ax+12b)= | | (-2xy)(-6x)= | | ax+x= | | (a-5x/2a)-(8a-3x/2a) | | 15+2(y+x)=37 | | Y^4+21y^2-72=0 | | X-(0.25*X)=27 | | 180=(180-(7x-4))+(7x-4) | | 600x-.5x^2-(100x+2x^2)= | | 2(0)+3(0)+z=6 | | 2(x)+3(0)+0=6 | | 2(0)+3(y)+0=6 | | 4r^4*3r^4= | | u/6=v |

Equations solver categories